Towards a Safe and Respectful Campus: Perspectives of Multicultural Education - Chen, Hsuan-Jen (International Dialogues on Education Journal, 2018)
This paper argues that multicultural education is an essential way of creating a safe and respectful campus. Examined from the perspective of power relations, schools are viewed as a site that helps maintain existing power relations by reinforcing the assimilation ideology. A drawback of this is that only one set of perspectives is valued. As a result, students who are not part of the norm are more likely to be treated unfairly in school. This may impose a negative effect on their learning as school is not a safe environment for them. To create a safe and respectful campus, multicultural education has to be incorporated as it helps students foster multiple perspectives and learn to embrace diversity. This paper first defines multicultural education. Secondly, it illustrates why multicultural issues should be examined in the framework of power relations. Then, it focuses on exploring the assimilation ideology and the role schools play in the process of assimilation. In this section, it analyzes how students are endangered by assimilation, and the case of the Yeh Yong-Zi event in Taiwan is also examined. Finally, it discusses in what ways multicultural education could help establish a safe and respectful campus culture.